Representaciones sociales de la enfermedad de Chagas en comunidades en riesgo: Creencias, actitudes y prevención - Leon Canelón, Mani; Paez Rovira, Dario (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Research about social representations of Chagas Disease in endemic areas of Trujillo State, Venezuela, was carried out. It purposes was to identify shared beliefs and attitudes that would facilitate or interfere with community participation in preventive activities. A survey with Likert items was administered to 473 people and in-depth interviews with 21 prototype persons were carried out. We found that beliefs tend to focus on the vec1or of the disease and that the prototype context where the disease occurs was the most important and widespread representation. Beliefs and attitudes predicting preventive intentions were identified. Results are discussed mainly regarding the social functions of representations.